Mini-Simple Limbal Epithelial Transplantation Versus Conjunctival Autograft Fixation With Fibrin Glue After Pterygium Excision: A Randomized Controlled Trial. Issue 11 (November 2019) - Sati, Alok; Banerjee, Supriya; Kumar, Poninder; Kaushik, Jaya; Khera, Anurag
Abstract : Purpose: To compare the outcomes between mini-simple limbal epithelial transplantation (mini-SLET) and conjunctival autograft (CAG) fixation with fibrin glue after excision of pterygium. Methods: Ninety-two eyes with primary nasal pterygium were prospectively randomized into a CAG control arm and a mini-SLET study arm. Follow-up examinations were set at the first and third day, at weeks 1, 2, and 4, and at the third and sixth month after surgery. The primary outcome measure was the recurrence rate at 1, 3, and 6 months after surgery, whereas the secondary outcome measures were the intraoperative time, postoperative symptoms, and other complications. Results: Eighty-two eyes completed the 6-month follow-up interval. Of the 42 eyes that underwent CAG, 4 (9.5%) exhibited recurrences, whereas only 1 of the 40 eyes (2.5%) treated with mini-SLET had recurrence ( P = 0.358). The time taken for surgery in the study group (21.4 minutes) was greater as compared to the control group (15.1 minutes) ( P < 0.001). The postoperative median symptom (foreign body sensation, lacrimation, pain, and irritation) score in the CAG group was significantly more for all symptoms on day 1 and day 3; however, on day 7, it was significantly more for pain and irritation only. Except dellen formation (1 in each group), both groups exhibited different other complications, although less in the study group. Conclusions: The study group exhibited a positive trend of less recurrence with reduced postoperative symptoms and other complications. More similar studies are required in future to validate the results.